MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN PENALARAN MATEMATIS DENGAN LAPS-HEURISTIC DAN PENDEKATAN OPEN-ENDED - Rasyid Ridha, Moch. (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This article reports the findings from an experimental pretest-posttest control group design conducted by using open-ended approach with Logan avenue problem solving (LAPS)-Heuristic model to investigate students? mathematical problem solving and reasoning abilities. The study involved 88 grade-10 students from SMA in Bandung. The instrumens of this study are mathematical problem solving test and mathematical reasoning test. By using SPSS 2.0.0 and Microsoft Excel 2013, the study found the open-ended approach with Logan avenue problem solving (LAPS)-Heuristic was able to improve students? mathematical problem solving and reasoning abilities better than that of conventional approach. Students? mathematical problem solving and reasoning abilities were classified as mediocore. Furthermore, the study found there was medium correlation between mathematical problem solving and reasoning abilities.